Dr Jekyll and Mr Hyde - Stevenson, Robert Louis, 1850-1894 (Classics illustrated (Newbury (England)), 2016)
Presents a graphic novel retelling of Robert Louis Stevenson's classic tale about Dr. Jekyll who is transformed by taking a drug into the murderous monster, Mr. Hyde. Also includes theme discussions, a timeline, and study questions.